PENGARUH ALAT PERAGA TIGA DIMENSI SISTEM PEREDARAN DARAH MANUSIA TERHADAP PENINGKATAN KETERAMPILAN PROSES SAINS SISWA SMA: The Effect Of Three Dimensional Tools Of Human Circulatory System To Improve The Science Process Skills Of Senior High School Students - Arfianto, Fahruddin (Anterior Jurnal, 2017)
This study is required by students to understand directly the circulatory system in humans with the three dimensional tools of human circulatory system. The purpose of this study was to determine the effect of three dimensional tools on science process skills of human circulatory system on circulation process material of senior high school students. The design of this study used was pretest-posttest control group design, in this design, there were two groups selected at random, then given pretest and postes. The study was conducted at SMA Muhammadiyah 1 Palangka Raya. The period of this study was July 2014 - April 2015. The sample of the study was the students of SMA Muhammadiyah 1 Palangka Raya in XI class on the first semester, as many as two classes of experimental class and control class with the number of control class students was 29 students, experimental class was 21 students. Data collection was tested with multiple choice questions tomeasure students’ learning outcomes, observation sheet to measure students' science process skill and using N gain then analyzed by t test. The results showed that the three dimensional tools of human circulatory system has a very significant effect on the improvement of science process skills with the most dominant indicator is in the observation. Based on the result of the study can be concluded that the use of three dimensional tools of human circulatory system can improve the science process skills of senior high school students.